Use of starch manufacturer residue in the production of inoculating biofertilizer - Bueno, Paulo Agenor Alves; Balestri, Edgar Lopes; Rosiello, Rafael de Almeida Vidal Feres; Silva, Cristian Coelho; Gualdi, Bruna Lopes; Oliveira, Vitória Maria Almeida Teodoro de; Cristófoli, Júlio Barreto; Sekine, Elizabete Satsuki; Bueno, Raquel de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
In the industrialization of cassava, effluents are generated capable of causing great impacts to the environment. One of these residues is called manipueira and its generation occurs by pressing the grated cassava mass. An alternative to the use of this industrial residue is its use as a culture medium in the multiplication of microorganisms useful in agriculture in the form of biological inoculants. The objective of this work was to evaluate the effectiveness of different concentrations of manipueira used as substrate in the development of the bacterium Bacillus subtilis and the fungus Trichoderma spp as biological control agents and plant growth promoters, aiming at the low cost of the agricultural protection process. The tests were carried out by means of a triple plating technique in culture medium containing manipueira, molasses and distilled water in different concentrations for both biological agents. The efficiency of the method, substract and organisms was measured through the calculation of colony forming units (CFU). The maximum production of CFU of the fungus Trichoderma spp was 1.2x109 CFU.mL -1 in a concentration of 175mL.L -1 of manipueira, while for the bacterium Bacillus subtilis, the maximum production reached 6.49x1011 CFU .mL -1 in culture with concentration of 125mL -1 of the residue. Compared to commercial inoculants with concentration around 1x108 CFU, the tested cultures were compatible with this value and still managed to overcome it, confirming its efficiency. Therefore, this is an excellent possibility to direct the use of environmental liabilities and to encourage the use of the biofertilizer by farmers who can produce it in their properties in an alternative way and with a low cost of production in relation to the commercial value.